2012
DOI: 10.4049/jimmunol.1100605
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Epithelial Cells Express Specific Ligands for Mucosal Macrophage Immunosuppressive Receptors Siglec-7 and -9

Abstract: Immune cells are known to express specific recognition molecules for cell surface glycans. However, mechanisms involved in glycan-mediated cell–cell interactions in mucosal immunity have largely been left unaccounted for. We found that several glycans preferentially expressed in nonmalignant colonic epithelial cells serve as ligands for sialic acid-binding Ig-like lectins (siglecs), the immunosuppressive carbohydrate-recognition receptors carried by immune cells. The siglec ligand glycans in normal colonic epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 36 publications
2
70
0
Order By: Relevance
“…Previous analysis also identified Siglec-7 and -9 ligands present in colorectal cancer and also found a role for those Siglecs in the generation of tumor-associated macrophages (43). Moreover, inhibitory Siglecs, including Siglec-7 and, in a minor fraction, Siglec-9, are expressed on NK cells (6,44).…”
Section: Discussionmentioning
confidence: 97%
“…Previous analysis also identified Siglec-7 and -9 ligands present in colorectal cancer and also found a role for those Siglecs in the generation of tumor-associated macrophages (43). Moreover, inhibitory Siglecs, including Siglec-7 and, in a minor fraction, Siglec-9, are expressed on NK cells (6,44).…”
Section: Discussionmentioning
confidence: 97%
“…If the CD-68 antigen is not expressed solely in macrophages but also by NGs, the finding of MPO in CD-68 + cells is explained. This is important especially when physiology of intestinal immune system is studied [17].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about Siglec expression and function on NK cell subsets is still limited in terms of NK cell differentiation and maturation, and the role of Siglec ligand-receptor interactions in disease remains to be explored. Whether Siglec-7 and -9 ligands in human cancer are expressed on malignant or healthy cells is a subject of controversy (3,(25)(26)(27)(28), as is the related question as to whether absence of inhibitory Siglecligand interactions promotes or inhibits tumor progression, either by uncoupled immune stimulation or by inhibition of immune defense (10,(25)(26)(27). Here, we found that Siglec-7 and -9 ligands were significantly overexpressed on a broad range of human malignant cells of different histological types and that surface Siglec-7 and -9 ligand expression determined cytotoxicity of human primary NK cells against both NK cell-susceptible and -resistant tumor cells.…”
Section: Introductionmentioning
confidence: 99%